2008
DOI: 10.1590/s0100-204x2008000900014
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cordeiros e estimativa da digestibilidade do amido de dietas com diferentes fontes protéicas

Abstract: Resumo -O objetivo deste trabalho foi avaliar a infl uência de fontes protéicas sobre desempenho, características da carcaça e da carne de cordeiros confi nados, e estimar a digestibilidade do amido de rações com alta proporção de grãos. Foram distribuídos 28 cordeiros Santa Inês, em blocos completos ao acaso, de acordo com o peso vivo e a idade, no início do experimento. As fontes protéicas foram os farelos de: soja, amendoim, canola e algodão, em dietas isonitrogenadas com 90% de concentrado e 10% de volumos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
24

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 20 publications
0
6
0
24
Order By: Relevance
“…Jardim et al (2000) found that the more the gastric contents, the lower the digestibility of forage ingested by animals. This is also a determinant factor in carcass yield, which it is affected by speed of passage of the feed and fasting period (Queiroz et al, 2008). Araújo et al (2004), using low-quality diets, observed that dry matter intake increased with increasing capacity of the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…Jardim et al (2000) found that the more the gastric contents, the lower the digestibility of forage ingested by animals. This is also a determinant factor in carcass yield, which it is affected by speed of passage of the feed and fasting period (Queiroz et al, 2008). Araújo et al (2004), using low-quality diets, observed that dry matter intake increased with increasing capacity of the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of licury cake negatively influenced ECW and HCW (half carcass height), and LEA, consequently. Highly fermentable carbohydrates such as starch are important energy sources in ruminant feedlot systems because they foster carcass accumulation (Queiroz et al, 2008;Ítavo et al, 2014). Substituting corn for licury cake may have reduced this nutrient in the diet and, therefore, reduced LEA.…”
Section: Resultsmentioning
confidence: 99%
“…As médias encontradas para o GDM e CMS foram de 221 e 889 g, respectivamente, resultados que estão de acordo com os comumente encontrados para cordeiros da raça Santa Inês alimentados com dietas contendo alto teor de concentrado (Urano et al, 2006;Queiroz et al, 2008). O GDM verificado foi ligeiramente superior ao reportado por Rodrigues et al (2008a), que também avaliaram dietas com alto teor de concentrado (90% da MS) contendo PCD (68,4% da MS) e observaram GDM de 167 g, reforçando a ideia de que a PCUD in natura ou ensilada tem grande potencial como ingrediente energético na ração de cordeiros em terminação.…”
Section: Resultsunclassified